A simultaneous localization and tracking method for a worm tracking system - Kowalski, Mateusz; Kaczmarek, Piotr; Kabaciński, Rafał; Matuszczak, Mieszko; Tranbowicz, Kamil; Sobkowiak, Robert (Zielona Góra: Uniwersytet Zielonogórski)
The idea of worm tracking refers to the path analysis of "Caenorhabditis elegant" nematodes and is an important tool in neurobiology which helps to describe their behavior. Knowledge about nematode behavior can be applied as a model to study the physiological addiction process or other nervous system processes in animals and humans. Tracking is performed by using a special manipulator positioning a microscope with a camera over a dish with an observed individual.
Keywords: "Caenorhabditis elegans" behavior; worm tracking; computer vision; image processing; feature extraction